The New York City Fiscal Crisis: What Happened and What is to be Done? - Grämlich, Edward M. (American Economic Review, 2016)
The New York City fiscal crisis as it was played out in the nation's newspapers this year had all the elements of a first class drama. There was first of all the tension-would the city make it through its periodic financial hurdles, would the Ford Administration blink, what would happen if the city defaulted? Then there were the accusations was it the fault of Wagner, Lindsay, Beame, Rockefeller, Ford, the unions, or economic and social forces beyond the city's control? Then the controversy-the issue seemed ideally suited to split deficit spenders from budget balancers, soft-headed liberals from hardheaded accountants, eastern establishment intellectuals from the silent majority. Finally, though it did not capture as much press coverage, the crisis also graphically illustrated several basic issues in the economics of federalism that are now creeping into public finance textbooks-the proper role of local and national governments in stabilizing the economy and redistributing income, whether the federal or the state government has an obligation to protect the financial integrity of local governments, whether public expenditures can be effectively controlled in the short run. This paper discusses the city's fiscal plight in the context of all of these issues. I. How Big are the Deficits?